RAGAM BAHASA PADA MEDIA SOSIAL INSTAGRAM: KAJIAN SOSIOLINGUISTIK - Andi Fauzan Ihsan Shadiq; La Yani Konisi; Sulfiah; Asma Wati Ndita (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2025)
The problem in this research concerns the variety of languages ​​found on Instagram social media and the various characteristics of the linguistic varieties found on Instagram social media. This research aims to describe the variety of languages ​​and the characteristics of the various languages ​​present on the Instagram social network, finding the contribution of the various languages ​​on the Instagram social network. The research method used in this research is a qualitative research method with a descriptive approach. Meanwhile, the methods and techniques used to analyze the data are note reading and screen capture method. And the data presentation method used in this research is the observation method. The data search results are as follows: Language varieties according to their characteristics are divided into 8 focuses, namely as follows: (1) Writing words different from the original form, (2) Writing shortened words, (3) Writing sentences different from the original form, (4)) Writing shortened sentences, (5) Using symbols and numbers, (6) Using greetings, (7) Using other varieties of language, and (8) Using foreign languages. Furthermore, various slang languages ​​have been taken and are often used on Instagram based on the type and meaning, namely: In the prokem there are 4 words that have been chosen to represent the use of various languages ​​on Instagram, namely: @ memecomic.id "roasting", @jakartakeras "udh", @kendariinfo “matchday” @vidiongakakterbaru “guru”. The results of this analysis can contribute to the teaching of Indonesian at university.